Evaluation Of Education Policy In 2013 Curriculum Change - Alfi Sahroh (AIUA Journal of Islamic Education, 2020)
This paper describes the evaluation of the 2006 curriculum change policy to the 2013 curriculum policy. This type of writing is descriptive-analytical using data collection techniques from several research journals. Education policy evaluation is a series of activities to find out that an education policy is in accordance with predetermined criteria and can have a real impact on the audience as desired. The results of the writing found that the 2013 curriculum change policy was the answer to the improvement of the previous 2006 curriculum (KTSP). The curriculum is based on internal and external challenges that will be faced by the nation in the future. The 2013 curriculum is designed to develop and strengthen a balanced attitude of knowledge and skills to students.